Pharmaceutical Manufacturing Continuous Crystallization Procedures: A Review (Asian Journal of Pharmaceutics (AJP), 2023)
This academic publication provides an overview of constant crystallization of solutions in the pharmaceuticalindustry. The comparison of continuous versus batch crystallizers, their construction benefits and drawbacks, andthe addition of solid form framing to create a constantly focused interaction between digital advanced processtechnology technologies and chemical manufacturing functionalities were all covered in detail because of thebroad key knowledge spectrum of precipitation. In-depth discussion was also given to mechanistic multiscalemodeling, whose comprehension is crucial for the creation of future control applications. Process simulation andcrystallizer optimization are also covered in the multiscale modeling section describes the model-based provided,which also addresses the intensifying method. Techniques the last section, is taken into consideration. The readercan become familiar with research pieces and their outcomes, which have thus far created different emergingviewpoints, by reading the unique articles on a particular theme that is gathered, talked about, and contrasted inthe aforementioned primary categories. The pharmaceutical sector places a lot of emphasis on crystallization,and readers may already discover literature on continuous crystallization. However, due to the increasing trendtowards the synthesis of items with special features that cannot be produced using conventional methodologies,the current study has placed a greater emphasis on the construction of automatic control for the generation ofcertain fine chemicals. Continuous crystallization may also allow for intensification techniques, modeling foroptimization, “on-demand” production, and MPC. A classification study examines the literature.